Building Capacity of School Leaders : Strategies that Work—Jamaica’s Experience - Nannyonjo, Harriet (World Bank, Washington, DC, 2017)
This paper examines literature about good practices in developing capacity for school leadership, identifies key good practices in the Jamaica National College for Education Leadership Program and reports on leadership practices of principals who were trained under this program. Literature recommends, the following good practices many of which were also found in the Jamaica program: (i) standards-based curriculum emphasizing instructional leadership, organizational development and change management; (ii) field-based internships with skilled supervision; (iii) cohort groups that create opportunities for collaboration and teamwork in practice-oriented situations; (iv) active instructional strategies that link theory and practice, such as problem based learning through case studies; (v)competence-based training and certification; and (vi) strong partnerships with schools to support quality, field-based learning.